Recommendations For Carbon Economic Value Governance Regulation: A Normative Analysis Of Carbon Trading In Indonesia - Soeharso, Silverius Y; Sufiarina, Sufiarina; Chaniago, Jafar; Nursyamsudin, Nursyamsudin (LEGAL BRIEF, 2025)
: This research examines the weaknesses of carbon trading regulations in Indonesia, particularly within the framework of Law Number 32 of 2009 on Environmental Protection and Management (UUPPLH) in the context of climate change mitigation. Indonesia, as a country that has ratified the Paris Agreement, faces challenges in regulating carbon trading mechanisms to reduce greenhouse gas emissions. Although UUPPLH provides a legal basis for environmental management, it does not explicitly address carbon trading aspects, such as verification, monitoring, and transaction transparency. The study also recommends strengthening the legal system based on the principles of precaution, justice, and transparency, which would enhance the integrity of Indonesia's carbon market. The precautionary principle emphasizes the need for stricter environmental impact assessments to avoid unforeseen damage, while the principles of justice and transparency ensure equitable benefit distribution and open access for all stakeholders. By introducing clearer and more inclusive regulations, Indonesia is expected to manage carbon trading sustainably, reduce the potential for misuse, and effectively achieve emission reduction targets. This research also proposes improvements to policies to prevent carbon crimes and enhance oversight mechanisms. The research method used is normative juridical with legislative and conceptual approaches to analyze legal gaps and provide recommendations for strengthening regulations aligned with international legal principles and Indonesia's domestic needs.